2018
DOI: 10.7567/apex.11.032701
|View full text |Cite
|
Sign up to set email alerts
|

Tm3+-doped barium gallo-germanate glass single-mode fiber with high gain per unit length for ultracompact 1.95 µm laser

Abstract: Heavily Tm3+-doped barium gallo-germanate glass single-mode (SM) fibers were successfully drawn. A gain per unit length of 3.6 dB/cm at 1.95 µm was obtained. To the best of our knowledge, this is the highest gain per unit length reported for Tm3+-doped germanate glass SM fibers. A single-frequency fiber laser operating at 1.95 µm has been built using a 1.5-cm-long active fiber pumped by a 1568 nm fiber laser. The direct output power from the ultracompact laser cavity is 227 mW. The results show that the fibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Fiber laser has good beam quality, high laser efficiency, good heat dissipation, stability, and high reliability, which has been widely used in the fields of photo‐communication, remote sensing, laser surgery, high‐resolution spectroscopy, coherent laser radar systems, and so on 1–4 . However, when fiber lasers are used in a high‐energy ray irradiation environment, such as space exploration, 5–7 laser sensing, 8 and nuclear industry, 9 the darkening of the glass fibers appears, which is commonly referred to as radiation‐induce darkening (RD) phenomenon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiber laser has good beam quality, high laser efficiency, good heat dissipation, stability, and high reliability, which has been widely used in the fields of photo‐communication, remote sensing, laser surgery, high‐resolution spectroscopy, coherent laser radar systems, and so on 1–4 . However, when fiber lasers are used in a high‐energy ray irradiation environment, such as space exploration, 5–7 laser sensing, 8 and nuclear industry, 9 the darkening of the glass fibers appears, which is commonly referred to as radiation‐induce darkening (RD) phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber laser has good beam quality, high laser efficiency, good heat dissipation, stability, and high reliability, which has been widely used in the fields of photocommunication, remote sensing, laser surgery, highresolution spectroscopy, coherent laser radar systems, and so on. [1][2][3][4] However, when fiber lasers are used in a high-energy ray irradiation environment, such as space exploration, [5][6][7] laser sensing, 8 and nuclear industry, 9 the darkening of the glass fibers appears, which is commonly referred to as radiation-induce darkening (RD) phenomenon. RD has been recognized as a serious issue for the utility of laser devices in the radiation environment, which not only gives rise to optical excess loss from ultraviolet to visible even down to near-infrared spectral region 10,11 but also causes continuous decrease in the output power, efficiency, lifetime, and reliability of these fiber laser systems.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] To date, single-frequency DBR fiber lasers at ∼ 2 µm have been developed by using different Tm 3+ -doped glass fibers, such as silica, silicate and germanate glass fibers. [7,12,13] However, pure silica glass fibers have a low RE ion doping concentration because of the well-defined glass structure consisting of a [SiO 4 ] tetrahedron, which limits the gain of the resulting silica glass fibers. [14] In 2015, Fu et al demonstrated a 2 µm single-frequency DBR fiber laser based on a 1.9-cm long commercially available Tm 3+ -doped silica glass fiber; this had a maximum output power of 18 mW and a slope efficiency of 13.4% with respect to the absorbed pump of a 793 nm laser diode (LD).…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth (RE) ions doped glass, also known as laser glass, is an important component in the fabrication of fiber lasers, which has received much attention due to its extensive applications in lidar systems, medical surgery, remote sensing, and so on . Therefore, the efficient research of laser glass is critical to the development of fiber lasers .…”
Section: Introductionmentioning
confidence: 99%